Confronting life in literary guises: A study of Dante, Blake and Sartre. - Elsherif, Sherine Ismail (AUC Knowledge Fountain, 2016)
The aim of this thesis is to examine the notion of realism as discussed by Erich Auerbach in his two critical works, Mimesis: The Representation of Reality in Western Literature and Dante: Poet of the Secular World. My interpretation of Auerbach is applied to Dante’s Inferno, cantos V, X and XXXIII, William Blake’s companion poems, “The Chimney Sweeper” I and II, in Songs of Innocence and Songs of Experience and Jean-Paul Sartre’s existentialist play, No Exit. In addition, Blake’s illustration of these three cantos from Dante’s epic will be examined to clarify how Blake’s poetics harmonized or clashed with that of Dante. The works of both Dante and Sartre take place in Hell, thus providing us with comparable versions of literary realism. Realism in this sense is subjective, psychological and personal; it pertains to the reality of a person’s essence and how, even in the afterlife, a person can retain his or her own character. Similarly, Blake’s poems demonstrate how a certain conception of the life after death is envisioned by the chimney sweeps. Their inability to appreciate the possibility of renewed existence demonstrates how literary realism can relate a failure in insight to a sense of closure. While examining important works by all three authors, the thesis expands on the usual meaning of literary realism to show how spiritual truths pertain to matters of life and death, public experience and personal morality.